PENGARUH KEPEMIMPINAN KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU DI SMA NEGERI 3 KONAWE SELATAN - Yanti, Murni; Z, Muslimin; Suharlian, Suharlian (Sultra Journal of Economic and Business, 2023)
This study aims to determine the effect of principal's leadership on teacher work discipline at SMA Negeri 3 Konawe Selatan. The sample in this study were 60 respondents who were all teachers at SMA Negeri 3 Konawe Selatan. This study uses simple regression analysis as an analytical tool. The results of this study found that the principal's leadership had a positive and significant effect on teacher work discipline with a value of 40.6%.